A prática pedagógica do/a professor/a de Matemática : as concepções dos/as professores/as do nono ano do ensino fundamental da rede pública estadual na cidade de Primavera do Leste-MT - Reis, Cássio João Lourenço dos (2020)
This research is linked to the Postgraduate Program in Education, (PPGEdu / CUR / UFMT), in the line of Teacher Training and Educational Public Policies and has as object of study the pedagogical practice of the Mathematics Teacher in the 9th grade of public elementary school in Primavera do Leste - MT. The main relevance of this investigation is in the fact that it contributes to the studies inherent in making teachers of teachers in the area of Mathematics. Therefore, the guiding problem of this investigation is: what is the conception that the Mathematics Teacher has in relation to his pedagogical practice in the classroom space? The general objective of the research is to understand the conceptions of teachers and Mathematics teachers in relation to their pedagogical practice in the classroom space. Based on the general objective, there are the following specific objectives: to investigate how the teacher evaluates his pedagogical practice in the school space; verify how the teacher develops his pedagogical practice; analyze the conception of Mathematics that guides the pedagogical practice of the teacher in the classroom and; reflect on the challenges of the teacher to teach mathematics in the 9th grade of elementary school. The research is outlined by the qualitative approach, based on the dialectical perspective of Paulo Freire's educational theory. For data collection, document analysis, semi-structured interviews and on-site observation of the class were used. The main theoretical and methodological framework used was Freire (2019; 2019a; 2018; 2009; 2008; 1995; 1991; 1979 1979a); in addition to other authors who agree with Freire, such as Carvalho (2019; 2012; 2010; 2005) Franco (2016; 2012; 2008); Gadotti (1997; 2001); Imbernón (2010; 2009); Paro (2008), among others; in addition to authors who bring the perspective of teaching mathematics, in this bias, such as: Bitencourt (2017); Diniz (2001); D’Ambrósio (2010; 2005; 2002); and Fiorentini (2003; 1995). The development of the research was to understand what the conception of pedagogical practice that teachers have, in addition to the challenges and possibilities for teaching Mathematics with an emancipatory bias of the subject. The research design was initially structured in order to organize it theoretically and methodologically, later data collection was carried out in three structuring axes, namely: document analysis, semi-structured interview and observation of the teachers' class. The main difficulty in the process of theoretical systematization of the data collected was due to little understanding or theoretical misunderstandings of the function of the educational institution, much of this is due to the working conditions imposed on teachers of Basic Education today. Other factors that should be noted are the importance attached to concepts related to pedagogy, as important elements in the teaching of mathematics, especially in the aspect of the absence of these concepts in the initial training of mathematics teachers. The results of this research pointed to the need to better understand the intentionality of the public school that, due to the teachers' working conditions, they end up worrying about bureaucratic elements of teaching than with their pedagogical practice.